Remoção e recuperação de nitrogênio amoniacal de efluente gerado no processamento do couro - Taki Filho, Paulo Kiyoshi (2015)
Industrial processing of leather is a sector with high potential of water, air and soil pollution. The wastewater is characterized by a mix of substances, making treatment complex. As for nitrogen, by the high values of pH and concentration, attendance patterns of release in legislation can be compromised, and become a returning inhibitor in biological treatment processes, intensively used by the industry. This research aimed to segregate deliming effluent removing substances stage, the largest source of nitrogen in the process, and promote their removal by air stripping and subsequent recovery in scrubbers. The air stripping tower was built with 150 mm diameter polyvinyl chloride (PVC) and operated in batch (5 L of wastewater) under controlled conditions of temperature, air flow (Qar) and initial pH (pHo). In the first stage were tested two configurations of filling material (GE and ECR), with the objective of determining their influence the removal of nitrogen ammonia (NAT) and estimating the mass transfer coefficient (KLA) in different Qar. The results showed that the fillings used showed similarity on the removal of the conditions studied NAT (pH = 12.2 and 25 ° C). For GE and ECR, the elevation of Qar 10 L min-1 for 25 L min-1 resulted increased removal efficiencies of 23.1% and 24.7% to 66.1% and 66.5% after 12 hours of experiment and KLA values of 0.1053 h-1 and 0.1131 h-1, respectively. There was a correlation between the removal of N-NH3 with decreasing alkalinity, with average value of 4 mgCaCO3mg N-NH3-1. In the second stage it was intended to study the influence of temperature, Pho and Qar in removing NAT and evaluate the system to absorb ammonia in the gas washing bottle filled with sulfuric acid 0.2 M. To the 20 trials was applied Rotational Central Composite Delineation (DCCR). After 12-hour-experiment, efficiency was achieved 83.7% at Qar 41L min-1, pHo 12.2 and temperature of 31 ° C. So, generally smaller efficiencies were observed with pHo below 10. It was possible to propose mathematical models that represent operating conditions tested, with a confidence level of 95%. The scrubber was effective in the recovery of ammonia (near to 100%), with the formation of ammonium sulfate.